Tratamento de lixiviado através de filtro anaeróbio associado a membrana de microfiltração - Dacanal, Marisa (My University, 2014)
Nowadays, the use of membrane bioreactors (MBRs) has been researched in many places of the world to treat different kinds of wastewater. The use of MBRs has advantages over other processes when the main focus is on the reuse of wastewater, small areas for wastewater treatment plant or restricted laws conditions. Commonly, the MBRs have been designed with suspended biomass. The goal of this work was to evaluate the performance of anaerobic reactor and anaerobic reactor associated with microfiltration membrane treating sanitary landfill leachate in pilot scale. The microfiltration membrane material used was ceramic (...) and its pore diameter and filtration area were 0.2 µm and 0.0094 m2, respectively. The retentate of the microfiltration unity was returned to the anaerobic reactor associated with microfiltration membrane. The results obtained in this research indicated that it is possible to treat leachate with this MBR configuration with a short hidraulic retention time (2.04 d). The mean value of COD concentration was 10,349 mg O2/L at the inlet of both reactors and the volumetric organic load for both reactors was 5.07 +- 2.90 kg DQO/m3.d. The membrane anaerobic reactor efficiency of COD removal was 90.4% as the mean value, against 21.5% of the anaerobic reactor. The efficiency of turbidity removal in the anaerobic reactor associated with microfiltration membrane was 90.3% with outlet values of 2.0 +- 2.0 NTU. Suspended solid concentrations at the outlet were higher in the anaerobic reactor than in the anaerobic reactor associated with microfiltration membrane, despite its higher upflow velocity. The analysis of biomass of both reactors showed that there was a better distribution of biomass in the anaerobic reactor associated with microfiltration membrane than the anaerobic reactor without microfiltration membrane, due to retentate recicling. The upflow velocity was 0.05 m/h in the anaerobic reactor and 31.5 m/h in the anaerobic reactor associated with microfiltration membrane. The main effect of these upflow velocity values was in the Reynolds number which was 2.9 for the anaerobic reactor and 1,799 for the anaerobic reactor associated with microfiltration membrane. Although both reactors had been designed to perform a laminar flow, the higher value of Reynolds number of the anaerobic reactor associated with microfiltration membrane produced a higher mass transfer coefficient and a better substrate utilization rate than the anaerobic reactor without microfiltration membrane. This is a reason, along with the retention of biomass and macromolecular compounds, that explains a better performance of the anaerobic reactor associated with microfiltration membrane. The results of modified fouling index (MFI) indicated that this index changed during the process, probably due the changes of pressure and compounds in the leachate. The anaerobic reactor associated with microfiltration membrane is a new option of wastewater treatment process, efficient, secure and an environmentally right alternative.
Atualmente, o uso de bioreatores associados a membranas (MBRs) tem sido pesquisado em muitos lugares do mundo para tratar diferentes tipos de efluentes. O uso de MBRs tem vantagens sobre outros processos quando o principal foco está na reutilização do efluente, pequenas áreas para o tratamento de efluentes ou condições restritivas da legislação. Normalmente, os MBRs são projetados com biomassa suspensa. O objetivo deste trabalho foi avaliar a performance de um reator anaeróbio e um reator anaeróbio associado a membrana de microfiltração tratando lixiviado de aterro sanitário em escala piloto. O material utilizado na membrana de microfiltação foi cerâmica (ver formula no documento original), com diâmetro de poro e área de filtração de 0,2 µm e 0,0094 m2, respectivamente. O rejeito da unidade de microfiltração retornava para o reator anaeróbio associado a membrana. Os resultados obtidos nesta pesquisa indicaram que é possível tratar lixiviado com esta configuração de MBR com um curto tempo de detenção hidráulica (2,04 d). O valor médio da concentração de DQO foi 10.359 mg O2/L na entrada dos reatores e, a carga orgânica volumétrica aplicada aos reatores foi de 5,07 mais ou menos 2,90 kg DQO/m3.d. A eficiência de remoção de DQO do reator anaeróbio associado a membrana foi de 90,4% como valor médio, contra 21,5% do reator anaeróbio. A eficiência de remoção de turbidez no reator anaeróbio associado a membrana de microfiltração foi de 90,3% apresentando valores de saída de 2,0 mais ou menos 2,0 NTU. Concentrações de sólidos suspensos na saída foram maiores no reator anaeróbio do que no reator anaeróbio associado a membrana, apesar da maior velocidade ascensional deste. A análise da biomassa dos reatores mostrou que houve uma melhor distribuição desta no reator anaeróbio associado a membrana de microfiltração do que no reator anaeróbio sem a membrana, devido ao reciclo do rejeito. A velocidade ascensional foi de 0,05 m/h no reator anaeróbio e 31,5 m/h no reator anaeróbio associado a membrana. O principal efeito destes valores de velocidade ascensional está no número de Reynolds calculado, o qual foi 2,9 para o reator anaeróbio e 1.799 para o reator anaeróbio associado a membrana. Embora ambos os reatores tenham sido projetados para atuar em fluxo laminar, o maior valor do número de Reynolds do reator anaeróbio associado a membrana produziu um maior coeficiente de transferência de massa e uma melhor taxa de utilização de substrato do que no reator anaeróbio sem a membrana. Este fato, juntamente com a retenção de biomassa e de compostos macromoleculares, explica uma melhor performance do reator anaeróbio associado a membrana de microfiltração. Os resultados do índice modificado de fouling (MFI) indicaram que este índice variou durante o processo, provavelmente devido a variações da pressão e de compostos presentes no lixiviado. O reator anaeróbio associado a membrana estabelece uma nova alternativa de tratamento de efluentes, eficiente, segura e ambientalmente correta.
Keywords: Resíduos sólidos, domésticos e industriais; Resíduos sólidos urbanos; Tratamento de resíduos; Aterro sanitário; Lixiviado; Tratamento anaeróbio; Processo anaeróbio; Compostos tóxicos